Polish Jokes about Americans - Brzozowska, Dorota (Investigationes Linguisticae, 2004)
The objective of the present paper is to analyze the character of Polish jokes about Americans and to find out what these jokes say about Poles. The latter question results from the assumption that stereotypes reveal more about those who propagate them than about those who allegedly represent particular traits. The popularity of Americans is a certain novelty in contemporary Polish jokes and this fact could be interpreted as another element in the processes of so-called McDonaldization. The texts are presented by the chronology of events they refer to. Americans are perceived by Poles as the enemies of the Russians, and so as a positive protagonist, a symbol of the high standard of living and an embodiment of the dream of success and freedom. Wide open spaces and big American cities, cowboys, Indians, Hollywood and Coca Cola are other symbols frequently occurring in jokes. AIDS and drug addictions are also supposed to be the products of America altogether with American right to carry arms, litigiousness and death penalty. Another feature of the Americans readily exploited by scoffers is a relatively short history and the hypocrisy of American political correctness. The general image of an American emerging from the analyzed jokes is largely positive and definitely more colorful than the image of a Pole in American jokes. Contextual references included in jokes show the knowledge of the Poles about America. And it does not really matter if this knowledge sometimes seems to be only a reflection of the image created and widespread by and for the use of the Americans themselves.